Bibliometric Analysis of Human Development and Local Wisdom: Global Trends and Insights - Zuhri , Saifudin (Journal of Information Systems Research and Practice, 2024)
This study aims to conduct a bibliometric analysis of scientific literature on human development and local wisdom over the past decade to identify trends, patterns, and key themes in the research. Utilizing a descriptive bibliometric research design, the analysis encompassed 210 article publications sourced from the Scopus database. The study employed quantitative bibliometric techniques to explore publication patterns, citation metrics, collaboration networks, and thematic developments. Data visualization was performed using VOSviewer to facilitate the interpretation of co-authorship networks, keyword co-occurrence, and citation relationships. The analysis revealed a substantial increase in research publications on human development and local wisdom from 2014 to 2024, with a notable peak in 2021. Indonesia emerged as the leading contributor, followed by the United States and China. The keyword analysis highlighted core themes such as sustainability, ecological wisdom, community development, and education, indicating a multidisciplinary approach in addressing human development issues. Collaborative networks were prominent, with significant contributions from specific author clusters. The study underscores the growing recognition of local wisdom’s importance in human development research. It highlights the necessity of interdisciplinary collaboration and integrating local knowledge into sustainable development practices. The findings provide valuable insights for future research directions, promoting culturally relevant and sustainable solutions to global challenges.